CT Scan Does Not Differentiate Patients with Hepatopulmonary Syndrome from Other Patients with Liver Disease - Chen, Yingming Amy; Prabhudesai, Vikramaditya; Castel, Helene; Gupta, Samir (PLOS ONE, 2016)
Background Hepatopulmonary syndrome (HPS) is defined by liver dysfunction, intrapulmonary vascular dilatations, and impaired oxygenation. The gold standard for detection of intrapulmonary vascular dilatations in HPS is contrast echocardiography. However, two small studies have suggested that patients with HPS have larger segmental pulmonary arterial diameters than both normal subjects and normoxemic subjects with cirrhosis, when measured by CT. We sought to compare CT imaging-based pulmonary vasodilatation in patients with HPS, patients with liver dysfunction without HPS, and matching controls on CT imaging. Methods We performed a retrospective cohort study at two quaternary care Canadian HPS centers. We analyzed CT thorax scans in 23 patients with HPS, 29 patients with liver dysfunction without HPS, and 52 gender- and age-matched controls. We measured the artery-bronchus ratios (ABRs) in upper and lower lung zones, calculated the “delta ABR” by subtracting the upper from the lower ABR, compared these measurements between groups, and correlated them with clinically relevant parameters (partial pressure of arterial oxygen, alveolar-arterial oxygen gradient, macroaggregated albumin shunt fraction, and diffusion capacity). We repeated measurements in patients with post-transplant CTs. Results Patients had significantly larger lower zone ABRs and delta ABRs than controls (1.20 +/- 0.19 versus 0.98 +/- 0.10, p<0.01; and 0.12 +/- 0.17 versus -0.06 +/- 0.10, p<0.01, respectively). However, there were no significant differences between liver disease patients with and without HPS, nor any significant correlations between CT measurements and clinically relevant parameters. There were no significant changes in ABRs after liver transplantation (14 patients). Conclusions Basilar segmental artery-bronchus ratios are larger in patients with liver disease than in normal controls, but this vasodilatation is no more severe in patients with HPS. CT does not distinguish patients with HPS from those with uncomplicated liver disease.